Stereoselective synthesis of fused tetrahydroquinazolines through one-pot double [3 + 2] dipolar cycloadditions followed by [5 + 1] annulation - Zhang, Xiaofeng; Pham, Kenny; Liu, Shuai; Legris, Marc; Muthengi, Alex; Jasinski, Jerry P.; Zhang, Wei (Beilstein Journal of Organic Chemistry, 2016)
The one-pot [3 + 2] cycloaddition of an azomethine ylide with a maleimide followed by another [3 + 2] cycloaddition of an azide with the second maleimide gives a 1,5-diamino intermediate which is used for a sequential aminomethylation reaction with formaldehyde through [5 + 1] annulation to afford a novel polycyclic scaffold bearing tetrahydroquinazoline, pyrrolidine, pyrrolidinedione, and N-substituted maleimide in stereoselective fashion.
Keywords: [5 + 1] annulation; [3 + 2] cycloaddition; one-pot reactions; stereoselective synthesis; tetrahydroquinazoline

(untitled) - Clarke, P. A.; Santos, S.; Martin, W. H. C. (Green Chem., 2007)

(untitled) - Bhuyan, D.; Sarma, R.; Dommaraju, Y.; Prajapati, D. (Green Chem., 2014)

(untitled) - Prasanna, P.; Perumal, S.; Menéndez, J. C. (Green Chem., 2013)

(untitled) - Zhang, X.; Zhi, S.; Wang, W.; Liu, S.; Jasinski, J. P.; Zhang, W. (Green Chem., 2016)

(untitled) - Weng, J.; Wang, S.; Huang, L.-J.; Luo, Z.-Y.; Lu, G. (Chem. Commun., 2015)

(untitled) - Cioc, R. C.; Ruijter, E.; Orru, R. V. A. (Green Chem., 2014)

(untitled) - Rotstein, B. H.; Zaretsky, S.; Rai, V.; Yudin, A. K. (Chem. Rev., 2014)

(untitled) - Estévez, V.; Villacampa, M.; Menéndez, J. C. (Chem. Soc. Rev., 2014)

(untitled) - Dömling, A.; Wang, W.; Wang, K. (Chem. Rev., 2012)

(untitled) - Brauch, S.; van Berkel, S. S.; Westermann, B. (Chem. Soc. Rev., 2013)

(untitled) - Gu, Y. (Green Chem., 2012)

(untitled) - Anastas, P.; Eghbali, N. (Chem. Soc. Rev., 2010)

(untitled) - Nicolaou, K. C.; Chen, J. S. (Chem. Soc. Rev., 2009)

(untitled) - Nicolaou, K. C.; Edmonds, D. J.; Bulger, P. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Padwa, A.; Bur, S. K. (Tetrahedron, 2007)

(untitled) - Enders, D.; Grondal, C.; Hüttl, M. R. M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wasilke, J.-C.; Obrey, S. J.; Baker, R. T.; Bazan, G. C. (Chem. Rev., 2005)

(untitled) - Werner, S.; Nielsen, S. D.; Wipf, P.; Turner, D. M.; Chambers, P. G.; Geib, S. J.; Curran, D. P.; Zhang, W. (J. Comb. Chem., 2009)

(untitled) - Zhang, W.; Lu, Y.; Chen, C. H.-T.; Curran, D. P.; Geib, S. (Eur. J. Org. Chem., 2006)

(untitled) - Lu, Q.; Huang, X.; Song, G.; Sun, C.-M.; Jasinski, J. P.; Keeley, A. C.; Zhang, W. (ACS Comb. Sci., 2013)

(untitled) - Lu, Q.; Song, G.; Jasinski, J. P.; Keeley, A. C.; Zhang, W. (Green Chem., 2012)

(untitled) - Hashimoto, T.; Maruoka, K. (Chem. Rev., 2015)

(untitled) - Seidel, D. (Acc. Chem. Res., 2015)

(untitled) - Coldham, I.; Hufton, R. (Chem. Rev., 2005)

(untitled) - Pellissier, H. (Tetrahedron, 2007)

(untitled) - Narayan, R.; Potowski, M.; Jia, Z.-J.; Antonchick, A. P.; Waldmann, H. (Acc. Chem. Res., 2014)

(untitled) - Zhang, W. (Chem. Lett., 2013)

WO Patent - Marineau, J. J.; Bradner, J. E.; Zhang, W.; Qi, J.; Mckeown, M. R.; Fu, H.; Liu, S. (Inhibitors of transcription factors and uses thereof, 2015)

(untitled) - Olsen, J.; Seiler, P.; Wagner, B.; Fischer, H.; Tschopp, T.; Obst-Sander, U.; Banner, D. W.; Kansy, M.; Müller, K.; Diederich, F. (Org. Biomol. Chem., 2004)

WO Patent - Trotter, B. W.; Isaacs, R. (Quinazoline potassium channel inhibitors, 2015)

(untitled) - Rörsch, F.; la Buscató, E.; Deckmann, K.; Schneider, G.; Schubert-Zsilavecz, M.; Geisslinger, G.; Proschak, E.; Grösch, S. (J. Med. Chem., 2012)

(untitled) - Rashid, A.; Kuppa, A.; Kunwar, A.; Panda, D. (Biochemistry, 2015)

(untitled) - Zhang, W.; Lu, Y.; Geib, S. (Org. Lett., 2005)

(untitled) - Korshin, E. E.; Sabirova, L. A.; Levinb, Y. A. (Synthesis, 2012)

(untitled) - Göblyös, A.; Lázár, L.; Fülöp, F. (Tetrahedron, 2002)